1983
DOI: 10.1093/genetics/105.1.157
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS OF a MOUSE Α-Globin GENE MUTATION INDUCED BY ETHYLNITROSOUREA

Abstract: A DBA/2 mouse treated with ethylnitrosourea sired an offspring whose hemoglobin showed an extra band following starch gel electrophoresis. The variant hemoglobin migrated to a more cathodal position in starch gel. Isoelectric focusing indicated that chain 5 of the mutant hemoglobin migrated to a more cathodal position than the normal chain 5 from DBA/2 mice and that the other α-globin, chain 1, was not affected. On focusing gels the phenotype of the mutant allele, Hbay  9, was expressed without dominance to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Animal studies have revealed the biological importance of A-T transversion mutations. The A-T -* T-A transversion event has been proposed to account for two mutations of the mouse a-and /5-globin genes arising in the progeny of ENUtreated female mice (Popp et al, 1983;Lewis et al, 1985).…”
mentioning
confidence: 99%
“…Animal studies have revealed the biological importance of A-T transversion mutations. The A-T -* T-A transversion event has been proposed to account for two mutations of the mouse a-and /5-globin genes arising in the progeny of ENUtreated female mice (Popp et al, 1983;Lewis et al, 1985).…”
mentioning
confidence: 99%
“…By contrast, no GC to AT changes have been found induced by ENU in the mouse germ line. The only ENU-induced germ-line mutations characterized to date have been in the globin genes, and their nature has been deduced from changes in the protein sequence (POPP et al 1983;LEWIS et al 1985;PETERS et al 1985;PETERS 1986). All are AT changes; two transversions to TA and two transitions to GC.…”
Section: Discussionmentioning
confidence: 99%
“…This research generated numerous mutant mouse strains, but because X-rays induce double-stranded breaks (DSBs) in DNA, the approach often caused large deletions and chromosomal rearrangements that affected multiple genes, making interpretation of the mutant phenotypes difficult (Silver 1995). Radiation has been supplanted by chemical mutagenesis with the DNA alkylating agent N-ethyl-N-nitrosourea (ENU), which is more mutagenic than X-rays (Russell et al 1979) and more likely to result in point mutations (Popp et al 1983). Because screening large numbers of mice in the G3 generation is so time-and labor-intensive, there are several modified approaches that allow for recovery of recessive mutations in the G2 generation.…”
Section: Forward Genetic Screensmentioning
confidence: 99%